Factors determine students' perception on cash Waqf awareness in Malaysia - Abdul Razak, Dzuljastri; Mohamed Imtiyaz, Mohamed Noordeen; Naji, Ariji; Azzam, Hamadah; Hassan, Fatimah; Syahidah, Ainul (World Academy of Islamic Management (WAIM), 2022)
The contribution of cash waqf, which had traditionally only been engaged in the empowerment of vacant land, has now become more varied and covering different areas of community welfare, such as health, education and business development. Although the purpose of the cash waqf program is important the presence of cash waqf and the waqf institution themselves are still not well known in the community, especially in educational field. As a result, the cash waqf program remained stagnant in achieving the goals of the Maqasid Syariah. Thus, the purpose of this paper is therefore to find out the factors that determine the students' perceptions of the cash waqf awareness in Malaysia, based on its acceptance, practice and expectations. The survey was provided to 342 respondents which were students of International Islamic University in Malaysia (IIUM) by conducting multiple linear regression examine the relationship between variables. The result shows that the, acceptance of the concept of cash waqf and expectations on efficient management of cash waqf affects students' perception on the cash waqf awareness in Malaysia.